Multiple waves of viral invasions in Symbiodiniaceae algal genomes. Issue 2 (26th October 2022) - Benites, L Felipe; Stephens, Timothy G; Bhattacharya, Debashish
Abstract: Dinoflagellates from the family Symbiodiniaceae are phototrophic marine protists that engage in symbiosis with diverse hosts. Their large and distinct genomes are characterized by pervasive gene duplication and large-scale retroposition events. However, little is known about the role and scale of horizontal gene transfer (HGT) in the evolution of this algal family. In other dinoflagellates, high levels of HGTs have been observed, linked to major genomic transitions, such as the appearance of a viral-acquired nucleoprotein that originated via HGT from a large DNA algal virus. Previous work showed that Symbiodiniaceae from different hosts are actively infected by viral groups, such as giant DNA viruses and ssRNA viruses, that may play an important role in coral health. Latent viral infections may also occur, whereby viruses could persist in the cytoplasm or integrate into the host genome as a provirus. This hypothesis received experimental support; however, the cellular localization of putative latent viruses and their taxonomic affiliation are still unknown. In addition, despite the finding of viral sequences in some genomes of Symbiodiniaceae, viral origin, taxonomic breadth, and metabolic potential have not been explored. To address these questions, we searched for putative viral-derived proteins in thirteen Symbiodiniaceae genomes. We found fifty-nine candidate viral-derived HGTs that gave rise to twelve phylogenies across ten genomes. We also describe the taxonomic affiliation of these virus-related sequences, their structure, and their genomic context. These results lead us to propose a model to explain the origin and fate of Symbiodiniaceae viral acquisitions.